2009
DOI: 10.1515/jpem.2009.22.11.1083
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Gonadal Dysgenesis in a 45,X Neonate with Chromosome Y Material in the Dysgenetic Gonad

Abstract: We report on a neonate with a disorder of sex development, Prader 3-4 external genitalia and a palpable structure in the right inguinal canal suggestive of gonadal tissue. Chromosome studies on blood lymphocytes showed monosomy of chromosome X. Laparoscopy identified a streak-like gonad on the left side, unicorn uterus and a dysgenetic testis on the right, attached to a Fallopian tube. Because of the unilateral palpable gonad and the presence of ambiguous genitalia we investigated further for the presence of Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Hence there is the need to use the fluorescence in situ hybridization (FISH) and the polymerase chain reaction (PCR) which can improve greatly the detection of low-frequency cell line and possible structural abnormalities. Peripheral blood lymphocytes are the material of choice for cytogenetic analysis on patients with monosomy X [3, 68]. In our case, the detection of Y material by PCR and FISH was negative.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Hence there is the need to use the fluorescence in situ hybridization (FISH) and the polymerase chain reaction (PCR) which can improve greatly the detection of low-frequency cell line and possible structural abnormalities. Peripheral blood lymphocytes are the material of choice for cytogenetic analysis on patients with monosomy X [3, 68]. In our case, the detection of Y material by PCR and FISH was negative.…”
Section: Discussionmentioning
confidence: 68%
“…The chromosome studies carried out on peripheral lymphocytes do not always reflect the proportion of cell lines in the gonads. The detection of Y chromosome material in a gonadal tissue could be necessary given the risk of malignant transformation [3, 6]. This complementary research in the gonadal tissue or another tissue (buccal mucosa) could not be performed in our case.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the presence of a double dose of the SRY gene initiated male sexual development, but the existence of a 45,X cell line affected the threshold of SRY expression needed to establish adequate testicular differentiation. On the other hand, Karatza et al [2009] reported a neonate with MGD presenting with ambiguous genitalia and a palpable gonad in the right inguinal canal with blood karyotypes showing a non-mosaic X monosomy, while the chromosome Y-derived sequence was detected in the dysgenetic gonad and skin fibroblasts by molecular analysis. They concluded that chromosome studies carried out on peripheral lymphocytes do not always reflect the proportion of cell lines in the gonads.…”
Section: Discussionmentioning
confidence: 99%